2017
DOI: 10.1111/nmo.13094
|View full text |Cite
|
Sign up to set email alerts
|

YH12852, a potent and highly selective 5‐HT4 receptor agonist, significantly improves both upper and lower gastrointestinal motility in a guinea pig model of postoperative ileus

Abstract: Oral administration of YH12852 significantly accelerates and restores delayed upper and lower GI transit in a guinea pig model of POI. This drug may serve as a useful candidate for the treatment of postoperative ileus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The 5‐HT system mainly consists of 5‐HT, 5‐HT receptor and the serotonin selective reuptake transporter (SERT). Blocking 5‐HT3R and 5‐HT4R, the excitatory 5‐HT receptor will lead to decreased gastrointestinal motility, whereas using agonists promotes gastric emptying (Morita et al ., 2013 ; Hussain et al ., 2017 ). The 5‐HT pathway also includes tryptophan hydroxylase (TPH‐1) and Toll‐like receptors (TLR).…”
Section: Introductionmentioning
confidence: 99%
“…The 5‐HT system mainly consists of 5‐HT, 5‐HT receptor and the serotonin selective reuptake transporter (SERT). Blocking 5‐HT3R and 5‐HT4R, the excitatory 5‐HT receptor will lead to decreased gastrointestinal motility, whereas using agonists promotes gastric emptying (Morita et al ., 2013 ; Hussain et al ., 2017 ). The 5‐HT pathway also includes tryptophan hydroxylase (TPH‐1) and Toll‐like receptors (TLR).…”
Section: Introductionmentioning
confidence: 99%
“…For example, bell shaped curve responses were reported in a study investigating the effects of a 5-HT4 agonist in a guinea pig model of postoperative ileus. 37 In conclusion, the concept that activation of luminal 5-HT 4 receptors could provide a safe and effective approach for the treatment of constipation is gaining momentum. 22 The findings described here reveal that novel, luminally acting 5-HT 4 R agonist compounds can generate prokinetic actions in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…This was not the case for the dose–response relationship in the in vivo whole gut transit and fecal output studies reported here, but this was not necessarily unexpected based on previous studies of this receptor. For example, bell shaped curve responses were reported in a study investigating the effects of a 5‐HT4 agonist in a guinea pig model of postoperative ileus 37 …”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10% of 5-HT is produced in the ENS and central nervous system, which stimulates the local intestinal nerve reflex, triggers secretion and propulsion and acts on the motor Ma et al Journal of Translational Medicine (2023) 21:349 vagal afferent nerve to regulate contractile activity [85]. Using a POI model of guinea pigs, one study has shown that treatment with 5-HT4 agonists before surgery can significantly accelerate intestinal movement and improve POI [86]. At the same time, a meta-analysis found that treatment with 5-HT agonists can promote intestinal recovery post-surgery [87].…”
Section: Gut Microbiota Affect the Ens By Regulating 5-htmentioning
confidence: 99%